Design and Evaluation of a New Fuzzy Control Algorithm Applied to a Manipulator Robot - Urrea-Onate, E; Kern-Molina, J; Alvarado-Neira, J (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
In this article, we propose a new scheme for a fuzzy logic controller, which includes acceleration as one of its linguistic variables, as opposed to other techniques and approaches that have been developed and reported in the literature. This method is used for controlling the tracking of the trajectory followed by the joints of a 2-DoF manipulator robot. To this end, a complete simulation environment is developed through the MatLab/Simulink® software. The dynamic model of the manipulator robot includes a vector that consists of the estimate of the friction forces present in the joints. Then, a controller based on fuzzy logic is designed and implemented for each joint. Finally, the performance of the developed system is assessed and then compared to the performance of a classic PID controller. The incorporation of the fuzzy variable acceleration significantly improved the system’s response. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.